Acute gastric necrosis caused by a β-hemolytic streptococcus infection: a case report and review of the literature. Issue 1 (2nd January 2020) - Kobus, Carolien; van den Broek, J. J.; Richir, M. C.
Abstract: Acute necrotizing gastritis, which appears to be a variant of phlegmonous gastritis is the rarest cause of gastric necrosis. We report a case of a 57-year-old female patient with an acute necrotizing gastritis caused by a Group A β-hemolytic streptococcus. The case presented herein is of unusual interest because only a limited number of case reports on this etiology have been published. Diagnosing infectious necrotizing gastritis remains complex because of its rarity and nonspecific clinical presentation. Nevertheless, prompt diagnosis is of high importance because necrotizing gastritis can progress rapidly into a more advanced stage causing septic shock or even death. In our opinion, early resection of necrotic gastric wall combined with adequate antimicrobial therapy is the cornerstone in treatment of necrotizing gastritis. We will present a case in which adequate medical treatment was not successful.